Malaria prevalence and incidence in an isolated, meso-endemic area of Mozambique - Jacques Derek Charlwood; Erzelia V.E. Tomás; Mauro Bragança; Nelson Cuamba; Michael Alifrangis; Michelle Stanton (PeerJ, 2015)
Isolated areas, such as the 2 × 7 km peninsula of Linga Linga in Mozambique, are the places where malaria might be most easily eliminated. Currently available control strategies include long-lasting insecticidal bednets impregnated with pyrethroid insecticides (LLINs), rapid diagnostic tests (RDTs) for diagnosis and artemisinin based combination therapy (ACT) for treatment and these were applied on the peninsula. In 2007, following a census of the population and mapping of 500 households, five annual all-age prevalence surveys were conducted. Information on LLIN use, house construction, and animal ownership was obtained. A spatially structured generalized additive model indicated that malaria risk was greatest towards the northern end of the peninsula and that people living in houses with grass or thatch roofs had a greater risk of malaria than those living in houses with corrugated iron roofs. Incidence peaked nine weeks after rainfall (r2 = 0.34, p = 0.0002). From 2009 incidence was measured at a centrally based project clinic. The proportion of under nine-year-old resident attendees diagnosed with malaria decreased significantly from 48% in 2009, to 35% in 2010 and 25% in 2011. At the same time, there was a shift in the peak age of cases from 1–4 year olds to 5–9 year olds. Nevertheless, in order to further reduce malaria transmission in an area such as Linga Linga, additional vector control measures need to be considered.